Shakhsiyyah Abdul Karim fi al tarbawiy "Rjalun tahta al Sifr" li MustafaMahmud :dirasah tahliliyyah sikilujiyyah adabiyyah li Sigmund Freud - Muchammmad Imam Rosyadi (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2015)
st,1/ws.c.1